Proceedings of the 7th International Conference on Communities and Technologies 2015
DOI: 10.1145/2768545.2768548
|View full text |Cite
|
Sign up to set email alerts
|

Community broadband initiatives

Abstract: Although access to broadband has become a facility embedded in everyday life, many communities still have poor or no connectivity, especially in rural areas. The paper considers how some local communities have taken matters into their own hands and set up their own community broadband infrastructure in the UK. The paper examines four case study rural communities in terms of the organisation of broadband provision. It identifies common skills and resources that were necessary in order for these community broadb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
(10 reference statements)
1
10
0
Order By: Relevance
“…We can therefore infer that leaders were critical in identifying other skills and assets in the community, often acting as conduits for individuals to network, participate and in turn become 'empowered'. This is reminiscent of the internal social capital identified by Wallace et al (2015) in their study of community broadband.…”
Section: Digital Champions and The Push For Better Broadbandmentioning
confidence: 88%
See 2 more Smart Citations
“…We can therefore infer that leaders were critical in identifying other skills and assets in the community, often acting as conduits for individuals to network, participate and in turn become 'empowered'. This is reminiscent of the internal social capital identified by Wallace et al (2015) in their study of community broadband.…”
Section: Digital Champions and The Push For Better Broadbandmentioning
confidence: 88%
“…From the perspective of the broadband installation, B4RN benefited from access to leaders with technical expertise within the community which facilitated planning of a technically robust fibre broadband network. This reflects the 'technological capital' identified as relevant for community broadband by Wallace et al (2015). This technical expertise in B4RN also contributed to an efficient and realistic installation plan that afforded the project credibility when attempts were made to secure funding from the community.…”
Section: Digital Champions and The Push For Better Broadbandmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the drivers of increases in fast broadband availability in sparsely populated localities could be diverse, and include factors other than geographical remoteness and settlement size. The delivery of community broadband schemes has been seen to depend on multiple forms of capital, such as appropriate skills, leadership and networking, and financial resources (Wallace et al, 2015). Additionally, locations in the USA with superior broadband coverage to their surroundings (or 'islands of availability') were distributed evenly across large and smaller urban areas and rural regions (Grubesic, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several animal and human studies revealed that anthocyanins have low bioavailability, compared to other flavonoids. [87] In vivo, ingested anthocyanins are absorbed very quickly in the stomach and intestine (about 5-20 min) and reach maximum plasma levels after ½ to 2 h. [24,88] Furthermore, most absorbed anthocyanins are in the intact glycosides forms. [24] Unabsorbed anthocyanins from stomach and intestinal epithelial cells reach the colon where they are actively metabolized by microorganisms.…”
Section: Overweight or Obese Malesmentioning
confidence: 99%